Tobacco smoking trends in Samoa over four decades: can continued globalization rectify that which it has wrought? - Christine Linhart; Take Naseri; Sophia Lin; Richard Taylor; Stephen Morrell; Stephen T McGarvey; Dianna J Magliano; Paul Zimmet (BMC, 2017)
Abstract Background The island country of Samoa (population 188,000 in 2011) forms part of Polynesia in the South Pacific. Over the past several decades Samoa has experienced exceptional modernization and globalization of many sectors of society, with noncommunicable diseases (NCD) now the leading cause of morbidity and mortality. The evolution of risk factor prevalence underpinning the increase in NCDs, however, has not been well described, including tobacco smoking which is related to cardiovascular disease, lung cancer, and chronic obstructive pulmonary disease. Methods The present study examines tobacco smoking in relation to different forms and effects of globalization in Samoa using 7 population-based surveys (n = 9223) over 1978-2013. Results The prevalence of daily tobacco smoking steadily decreased over 1978-2013 from 76% to 36% in men, and from 27% to 15% in women (p < 0.0001 both sexes). During 1991-2013, current tobacco smoking also steadily decreased from 64% to 40% in men (p < 0.0001), and from 21% to 17% in women (p < 0.05). Declines were similar in younger (25-44 years) and older (45-64 years) men and women. Colonial globalization facilitated the introduction and prolific spread of tobacco trade and consumption in the Pacific Islands from the sixteenth century, with many populations inexorably pulled into trade relations and links to the global economy. It has also been a different globalization which may have led to the decline in smoking prevalence in Samoa in recent decades, through global dissemination since the 1950s of information on the harmful effects of tobacco smoking derived from research studies in the USA and Europe. Conclusions Over the past 35 years tobacco smoking has steadily declined among Samoan adults; the only NCD risk factor to demonstrate marked declines during this period. By 2013 tobacco smoking in women had decreased to levels similar to Australia and New Zealand (ANZ), however in men smoking prevalence remained more than three times higher than ANZ. The impact on smoking prevalence of the variety of tobacco control interventions that have been implemented so far in Samoa need to be evaluated in order to determine the most effective initiatives that should be prioritized and strengthened.